BIOPHILIC DESIGN SEBAGAI PENEKANAN SPIRITUALITAS MANUSIA PADA DESAIN RUMAH RETRET KATOLIK DI KOTA BATU - James Efandaru; Heristama Anugerah Putra; Stefanus Prabani Setio Hastorahmanto (MODUL, 2026)
Changing  times  have  a  complex  impact  on  human  life. Even   though   there   are   many   positive   influences, negative  challenges  such  as  increasing  spirituality  due to the pressures of modern life are also increasingly felt, resulting  in  spiritual  forgetting.  In  this  situation,  the need  for  a  retreat  house  that  can  offer  physical  and spiritual    tranquility    and    recovery    becomes    very important.  The  research  aims  to  design  a  retreat  house in the city of Batu using a qualitative descriptive method approach,  which  focuses  on  in  depth  design  principles that   support   mental   and   spiritual   well-being.   By adopting  biophilic  architectural  principles,  it  is  hoped that  this  design  can  create  a  harmonious  relationship between   humans   and   nature,   while   supporting   the mental,   physical   and   spiritual   healing   process.   The uniqueness    of    this    retreat    house    lies    in    the implementation of integrated biophilic elements, such as water,  plants  and  natural  lighting  used  in  each  room. Facilities  are  designed  to  encourage  visitors  to  interact with    nature,    including    open    meditation    spaces, reflection paths amidst the  landscape, and prayer areas connected to the surrounding environment. The result of this  research  is  the  design  of  facilities  that  not  only focus  on  spiritual  activities,  but  also  provide  a  holistic retreat    experience,    with    an    emphasis    on    human interaction  with  nature  as  an  important  aspect  in  the healing process